PENGARUH CURRENT RATIO DAN DEBT TO TOTAL ASSET RATIO TERHADAP NET PROFIT MARGIN PADA PERUSAHAAN PT ASTRA OTOPARTS TBK PERIODE 2011 – 2021 - Mochamad Algam Alif Angkasa Algam; Lina Nofiana (Journal of Research and Publication Innovation, 2023)
This research aims to test the Current Ratio (CR) and Debt to Asset Ratio (Dar) on the Net Profit Margin (NPM) at the company PT. Astra Otopart Tbk in 2011-2021. Data obtained through financial reports (https://www.astra-otoparts.com/) in the form of financial reports that have been prepared by PT. Astra Otopart Tbk. This research uses descriptive quantitative methods with a sample of 11 years, namely annual financial reports for the period 2011-2021. Data analysis used simple linear regression analysis and multiple linear regression using SPSS version 26 software. Hypothesis testing using T test, F test, and Determination test. The results showed that partially Current Ratio (CR) had a significant negative effect on Net profit margin (NPM) with a calculated value of tcount (-2.580) > ttable (-2.306) and has a significant value of 0.033 <0.05. Meanwhile, the Debt to Asset Ratio (DAR) is not has a significant effect on Net Profit Margin (NPM) with a calculated value of tcount (2.027) < ttable (2.307) and has a significant value of 0.077 > 0.05, simultaneously Current Ratio (CR), Debt to Total Asset Ratio (DAR), no there is a simultaneous influence on Net Profit Margin (NPM) with a significance value of 0.063 > 0.05 with a value of fcount (3.985) < ftable (4.459) at the company PT. Astra Otopart TBK.